Gender Disparity and Occupational Roles in the Banking Sector: Social Work Opinion on Workforce Inequality (2023)
The connection between gender inequality and job roles among bank employees illustrates the complicated factors that sustain workplace disparities. This research investigated how gender- based imbalances appear in the banking industry, frequently leading to uneven representation, salary disparities, and fewer advancement opportunities for women. By delving into aspects like hiring practices, promotion criteria, work-life balance, and organizational culture, the study uncovers the primary obstacles that maintain gender-based occupational segregation. The results indicate that conventional gender expectations, hidden biases, and the absence of supportive workplace policies play significant roles in reinforcing this gap. Recommendations for reducing gender inequality among bank employees include implementing fair hiring and promotion practices, encouraging mentorship programmes, and advocating for workplace flexibility. Prioritizing the cultivation of an inclusive culture and addressing systemic barriers are essential for diminishing gender disparities and fostering a more diverse and fairer banking sector. This summary sheds light on the hurdles women encounter in the banking sector and offers approaches to foster greater gender balance and inclusion in the industry.